(3GdeSFhdjI GdLfGFjI ddCTNGU GdeYfhjI ai bGfhf ZSd GdCehGd GdeUQi GdbGfhf Qbe 80 dSfI 2002(B: s (3OQGSI ebGQfI (B/ s - (3CMeO YeQ eMeO eMeO SGdes; (3WGQb SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3JYO XGgQI ZSd GdCehGd ef GdXhGgQ GdMOjKI(B: (3Ch HJYHjQ COb ef GdXhGgQ GdNWjQI GdecJTaI MOjKG(B: (3aQHeG CfgG eYQhaI efP YghO SGHbI(B: (3h dcf GdJTQjYGJ GdeNJdaI de JJLg Edi ehGLgJgG EdG MOjKG(B: (3HYO Cf KHJ VQQgG GdeMOb Ydi GdeSJhjGJ GdSjGSjI h GdGbJUGOjI h GdGLJeGYjI h GdCNdGbjI (B... (3hdcf gPg GdehGLgI GNJdaJ ef JTQjY Edi BNQ(B: (3JHYG ddSjGSI GdLfGFjI GdJj JJHYgG GdOhdI(B. (3aef GdOhd ef JhSY aj gPg GdehGLgI HMjK GeJOJ Edi GdCehGd GdfGJLI ef Cj eUOQ ZjQ eTQhY ShGA CcGfJ GdLQjeI LfGFjI Ch LfMI Ch eNGdaI(B: (3Cj CjG cGfJ LSGeI GdLQjeI h WHjYJgG(B: (3ShGA CcGfJ ef LQGFe GdGYJOGA Ydi GdeUdMI GdYGeI Ch GdCehGd Ch GdCTNGUs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2013s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B159-167s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeSFhdjI GdLfGFjIs; (3ZSd GdCehGds; (3GdCSGS GdadSaj ddeSFhdjI GdLfGFjIs; (3GdTNU GdeYfhjs; (3GdCMcGe GdYGeIs; (3LQGFe ZSd GdCehGd aj GdJTQjY GdebGQfs; (3eOi GfWHGb GdCMcGe GdYGeIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs